2021
DOI: 10.1021/acs.nanolett.1c02074
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Multiphoton Processes in Perovskite Metasurfaces

Abstract: Multiphoton absorption and luminescence are fundamentally important nonlinear processes for utilizing efficient light−matter interaction. Resonant enhancement of nonlinear processes has been demonstrated for many nanostructures; however, it is believed that all higher-order processes are always much weaker than their corresponding linear processes. Here, we study multiphoton luminescence from structured surfaces and, combining multiple advantages of perovskites with the concept of metasurfaces, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 38 publications
0
55
0
Order By: Relevance
“…In addition, the threshold of two-photon emission was comparable with that of onephoton emission. [262] Zhao et al reported the two-photon pumped ASE from perovskite single crystal (Figure 15d). The threshold and optical gain of perovskite laser were 0.65 mJ cm −2 and 38 cm −1 .…”
Section: Light Emission Modulation With Photonic Structuresmentioning
confidence: 99%
“…In addition, the threshold of two-photon emission was comparable with that of onephoton emission. [262] Zhao et al reported the two-photon pumped ASE from perovskite single crystal (Figure 15d). The threshold and optical gain of perovskite laser were 0.65 mJ cm −2 and 38 cm −1 .…”
Section: Light Emission Modulation With Photonic Structuresmentioning
confidence: 99%
“…
Fig. 12 Light-emitting metasurfaces a Modal structure of symmetric and symmetry broken semiconductor metasurfaces [ 47 ], b Unidirectional luminescence from the InGaN/GaN quantum-well metasurface [ 48 ], c Active perovskite hyperbolic metasurface with deep-subwavelength alternating layers [ 49 ], d Light-emitting metalenses and meta-axicons for focusing and beaming of spontaneous emission [ 50 ], and e Enhanced multiphoton processes in perovskite metasurfaces [ 51 ]
…”
Section: Light-emitting Metasurfacementioning
confidence: 99%
“…demonstrated the enhanced multiphoton processes in perovskite metasurfaces, as shown in Fig. 12 e [ 51 ]. The proposed perovskite metasurfaces reveal a great efficiency in the nonlinear multiphoton processes, which is comparable to that in linear counterpart.…”
Section: Light-emitting Metasurfacementioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement of multiphoton-photoluminescence was also demonstrated in dielectric nanoantennas and metasurfaces, and was exploited for optical encoding using mid-index lead halide perovskite as the dielectric, as well as for mapping the magnetic field profile of the excitation beam . The imaging of anapole states and higher order modes inside dielectric nanoantennas through THG scanning was also demonstrated. , …”
Section: Nonlinear Wavefront Control and Imagingmentioning
confidence: 99%